Anatomical characteristics of the leaning stem in Pinus merkusii seedling - NEVLYA MIA SAFITRI; FANANY WURI PRASTIWI; SYIFA SALSABILA; YOGI FERIAWAN; ALIF BRILIANTO; WIDYANTO DWI NUGROHO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Safitri NM, Prastiwi FW, Salsabila S, Feriawan Y, Brilianto A, Nugroho WD. 2023. Anatomical characteristics of the leaning stem in Pinus merkusii seedling. Biodiversitas 24: 3796-3802. Pinus merkusii Jungh. & de Vriese is one of the tropical conifer species. The species formed reaction wood called compression wood (CW) when the stem grows in an abnormal position. CW in stem wood is frequently found to cause several problems for utilization in the use of its products. However, there are few studies on the anatomical characteristics of reaction wood in tropical conifer. This study aimed to observe the differences in anatomical characteristics between compression (CW) and opposite (OW) woods in leaning the stem of P. merkusii seedlings and their anatomical differences compared to normal wood (NW). Approx. 1-year-old P. merkusii seedlings from a nursery in Trenggalek, East Java, Indonesia, that were naturally bent or tilted were used in the study. Anatomical characteristics of wood, namely the dimension of tracheids, rays, resin canals, and the proportion of cells were observed in the study. The results showed that CW of P. merkusii seedlings formed a rounded tracheid shape and intercellular space. The differences between CW and OW in P. merkusii seedlings were significant in terms of height of ray cells, tracheid proportion, and resin canal proportion. However, tracheid length, tracheid diameter, tracheid wall thickness, resin canal diameter and frequency, rays frequency, and ray proportion were not significantly different compared to OW and NW.